2018
DOI: 10.1111/1471-0528.15502
|View full text |Cite
|
Sign up to set email alerts
|

Transversus abdominis plane block under laparoscopic guide versus port‐site local anaesthetic infiltration in laparoscopic excision of endometriosis: a double‐blind randomised placebo‐controlled trial

Abstract: ObjectiveTo compare the efficiency of laparoscopically guided transversus abdominis plane block (LTAP) versus port‐site local anaesthetic infiltration (LAI) in reducing postoperative pain following laparoscopic excision of endometriosis.DesignA prospective, double‐blind randomised controlled trial.SettingA tertiary referral centre for endometriosis and minimally invasive gynaecological surgery.PopulationWomen undergoing laparoscopic excision of endometriosis from December 2015 through July 2016.MethodsParticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The details of the methodological risk of bias assessment are presented in graphic and summary forms (Figures 2 and 3). In summary, 7 RCTs [10,15,17,20,[22][23][24] had a low risk of bias, and 8 RCTs [11-14, 16, 18, 19, 21] had an unclear risk of bias. The main reasons for the 8 RCTs having an unclear risk of bias were due to a failure to mention the following factors: randomization sequence generation, allocation concealment, blinding of participants and personnel, and blinding of outcome assessment.…”
Section: Risk Of Methodological Bias and The Quality Of Thementioning
confidence: 97%
See 1 more Smart Citation
“…The details of the methodological risk of bias assessment are presented in graphic and summary forms (Figures 2 and 3). In summary, 7 RCTs [10,15,17,20,[22][23][24] had a low risk of bias, and 8 RCTs [11-14, 16, 18, 19, 21] had an unclear risk of bias. The main reasons for the 8 RCTs having an unclear risk of bias were due to a failure to mention the following factors: randomization sequence generation, allocation concealment, blinding of participants and personnel, and blinding of outcome assessment.…”
Section: Risk Of Methodological Bias and The Quality Of Thementioning
confidence: 97%
“…BioMed Research International including general surgeries [10][11][12][13][14][15][16], gynecological and obstetric surgeries [17][18][19][20][21][22], urinary surgeries [23], and nephrology surgeries [24].…”
Section: Flowchart Of the Literature Search And Studymentioning
confidence: 99%
“…While studies suggest that these two intraoperative anesthetic methods could reduce postsurgical pain in gynecologic laparoscopic surgeries, only two studies from the US and Europe have reported that postsurgical pain outcomes comparing TAP and LA in gynecological laparoscopic surgeries and its effects on postoperative pain remain inconclusive. [ 9 10 ] Therefore, we conducted the first study to compare postoperative analgesic effects of intraoperative levobupivacaine local infiltration anesthesia and TAP block following gynecologic laparoscopy in Japanese population.…”
Section: Introductionmentioning
confidence: 99%
“… 13 14 Furthermore, the efficacy of laparoscopic TAP block was also compared to port-site injections in a number of studies, which showed mixed results, warranting continued investigation. 15 17 TAP block-related complications are extremely rare, including transient femoral nerve palsy, anesthetic systemic toxicity, bowel hematoma, and liver laceration. 18 19 Prior studies have shown that the majority of TAP block complications resulted from incorrect needle placement and suggested lower complications with direct visualization.…”
Section: Introductionmentioning
confidence: 99%